Enhancing In-crop Diversity in Common Bean by Planting Cultivar Mixtures and Its Effect on Productivity - Reinprecht, Yarmilla; Schram, Lyndsay; Smith, Thomas H.; Pauls, K. Peter (Frontiers in Sustainable Food Systems, 2020)
Common bean (Phaseolus vulgaris L.) is the most important food legume crop worldwide. Canadian beans, especially large seeded cultivars of Andean origin, have relatively narrow genetic diversities. Establishing crops with mixtures of cultivars instead of pure lines is a simple, cost effective way to increase genetic diversity in the field. A number of studies have demonstrated the benefits of mixture cropping over monocropping in controlling disease, increasing water use efficiency and increasing yield stability. The objective of this study was to determine the effects of increasing in-field diversity, by using mixtures of bean cultivars instead of monocultures, on productivity. The feasibility of growing bean cultivar mixtures in southern Ontario environments was confirmed with a small pilot study that was conducted with four bean cultivars and restricted number of mixtures at two locations in 2017. Mixture performance experiments were performed with seven diverse bean genotypes at two Ontario locations [Woodstock and Elora (two planting dates) research stations] as pure stands and all possible binary mixtures (planted in alternate rows or as completely random mixtures) in 2018. Conventional plot-based above ground crop data were collected. Mixing efficiencies were calculated from the yield data using a Relative yield of the mixture (RYM) index. Diallel analysis was used to identify general mixing ability of cultivars and specific mixing abilities of mixtures. Significant differences among seven bean cultivars and their mixtures were identified in all three environments for all analyzed traits. The results indicated multiple benefits of planting mixtures compared to monocultures A number of mixtures overyielded component cultivars grown in pure stands; they had higher yields, RYM index values greater than one and positive specific mixing abilities (for yield) in both types of biblends. The research has the potential to provide a theoretical basis for the use of precision agriculture tools to plant fields with mixtures instead of monocultures. It could lead to greater in-field diversity in the crop and in the above and below ground ecosystems that might provide greater buffering capacity and resiliency to the cropping system as well as increased ecosystem services.